First record of Genlisea (Lentibulariaceae) for Mexico - Olvera García, Martha; Martínez S., Esteban (Instituto de Ecología, A.C., 2002)
Genlisea filiformis A.St.-Hil. is reported for the first time from Mexico. Its distinctive characters, as well as information on its habitat and geographic distribution are presented.